(untitled) (SCIÉNDO INGENIUM, 2022)
The application of different sugar cane molasses conditions (yeast strain, antibiotic concentration and molasses pH) was aimed at obtaining the highest ethanol yield. In ethanol production, a 3x3x3 factorial design was used with 3 replicates per treatment, with antibiotic concentration levels: 10 ppm, 15 ppm and 20 ppm; pH: 4.6, 4.8 and 5.0 and yeast strains: Fleish-mann, Red Star and Fermipan Brown. The process applied involved molasses conditioning, fermentation and distillation. The results showed that the maximum ethanol yield (314.13 ± 8.77 L/MT of molasses) was obtained with the yeast strain Saccharomyces cerevisiae Fermipan Brown at pH 4.8 and antibiotic concentration of 15 ppm. In conclusion, the proposed treatment was shown to have a higher productivity in relation to the other proposed methods.